Evaluating the Relationship between Grit and Mathematics Academic Achievement among Senior High School Students - Joan B Mariano (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This study aimed to assess the grit level of senior high school students in a Philippine high school and to analyze its relationship with their academic achievement in Mathematics. Methodology: This study employed a quantitative descriptive-correlational research design. Data were gathered from Grade 12 students in the Cordillera Administrative Region (CAR), Philippines. The “Grit-S” Scale (Duckworth & Quin, 2009) was utilized with its reliability tested using Cronbach’s alpha (0.754). Sample size of 225 students was determined through Cochran’s formula. Data were treated using weighted mean and Pearson’s Product Moment of Correlation. Main Findings: Students exhibited moderate levels of grit (overall x̅ = 3.20) and very satisfactory mathematics achievement (x̅ = 85). Using Pearson’s Product-Moment Correlation, a weak but statistically significant positive relationship was found between grit and mathematics academic achievement (r = 0.20, p < 0.01), indicating that grit has a limited but measurable association with students’ performance. Novelty/Originality of this study: This study is among the first to investigate grit as a non-cognitive factor influencing Mathematics achievement in the Philippine senior high school context. By localizing the application of the Grit-S scale, it expands global research to a new cultural setting and highlights the role of perseverance in shaping academic outcomes, offering evidence-based insights for curriculum and instructional improvement.